Economic and institutional analysis of hybrid rice seed value chain inIndia: Evidence from Telangana: Hybrid rice seed value chain in India - SHEELAM, KAVI RAJU; Aldas, Janaiah; Ramalingareddy, Vijaya Kumari; Radhika, P; Chary, D Srinivasa (ORYZA-An International Journal of Rice, 2025)
This study analysed the institutional and economic dynamics of the hybrid rice seed industry in Telangana, India, during the 2021-22 summer season, with a focus on contractual arrangements in production and benefit distribution among stakeholders in hybrid rice seed value chain. Primary data from 196 seed growers, 60 organizers, and 10 companies across 30 seed villages revealed that hybrid rice seed enterprises predominantly operated under a centralized contract farming model. Of the 196 seed growers, 96.43% engaged in contracts, with 55.55% relying on verbal and 44.45% on written contracts, the latter proving more effective due to well defined terms. Institutional support played a pivotal role in enhancing productivity, with technical staff visits, contracts with multinational corporations, and written agreements positively influencing hybrid rice seed yield. Training participation had the most significant impact, underscoring the importance of capacity-building interventions in improving production efficiency. An analysis of benefit distribution indicated that seed companies captured the largest share (53.64%) of total economic gains, followed by seed dealers (20.23%), seed distributors (13.53%), seed growers (10.26%), and organizers (2.08%). The study recommends the establishment of a legal framework to formalize and enforce contracts, promoting written agreements for greater transparency in pricing and payment terms. Additionally, policies should mandate price transparency and equitable benefit-sharing mechanisms to ensure fair compensation for seed growers while optimizing costs and improving value distribution within the hybrid rice seed value chain.